PARTISIPASI PETANI DALAM PROGRAM UPAYA KHUSUS PENINGKATAN PRODUKSI PADI, JAGUNG, DAN KEDELAI (UP2PJK) DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Rizka Shafira Triana; Kordiyana K Rangga; Begem Viantimala (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2017)
The purpose of this research was to know the factors that associated with the level of farmer participation in UP2PJK program in Seputih Raman Subdistrict and the relationship between the level of farmer participation in UP2PJK program and rice productivity.  Data of this research was collected on Agustus-September 2016.  The respondents of this research were 83 of rice farmers who were choosen by simple random sampling method.  The analytical methods used in this research were descriptive and quantitative methods.  The result of this research shows that associating factors with the level of farmer participation in  UP2PJK program were knowledge of the program, frequency of  following extension activity, farmer motivation, and  level of cosmopolitness. There was no relationship between the level of farmer participation and productivity of rice in UP2PJK program in Seputih Raman Subdistrict Central Lampung Regency.Key words: participation, productivity, program